2021
DOI: 10.3390/buildings11030081
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of the Use of Construction Waste to Replace Conventional Aggregates in Concrete

Abstract: This work aims to study the influence of using construction and demolition waste in the replacement of coarse and fine aggregate to produce recycled aggregate concrete (RAC). A moderate compressive strength concrete made with usual fine and coarse aggregate was used as a benchmark material. Compressive and split tensile tests were performed using 120 cylindrical concrete specimens with 150 mm diameter and 300 mm length. Four-point flexural tests in reinforced beams made with conventional concrete and RAC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Fine residues containing binding particles often essentially increase the dosage of water and entirely reduce the final mechanical and durability performance of hardened concrete. However, Silva et al (2021) reported exactly the opposite trend, thus utilization of fine RA led to a similar mechanical performance in comparison with the reference mixture; respectively, utilization of coarse RA caused a significant decay [6]. Similar results were reported by Khatib (2005) [7].…”
Section: Introductionsupporting
confidence: 76%
“…Fine residues containing binding particles often essentially increase the dosage of water and entirely reduce the final mechanical and durability performance of hardened concrete. However, Silva et al (2021) reported exactly the opposite trend, thus utilization of fine RA led to a similar mechanical performance in comparison with the reference mixture; respectively, utilization of coarse RA caused a significant decay [6]. Similar results were reported by Khatib (2005) [7].…”
Section: Introductionsupporting
confidence: 76%
“…At the same time, in the process of engineering construction, the consumption of natural sand and stone has increased. To protect natural resources and deal with discarded construction waste, the reuse of construction waste has become a key topic in the field of concrete research internationally, which has attracted the attention of experts and scholars from around the world [2]. Recycling construction waste, crushing, cleaning, and screening into a recycled coarse aggregate (RCA) can not only save natural resources and reduce environmental pollution, but also reduce the cost of aggregate used in construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…Silva, F.A. et al [ 9 ] used recycled fine aggregates and recycled coarse aggregates to replace ordinary aggregates, considering different replacement rates, and found that the replacement of ordinary coarse aggregates with recycled coarse aggregates had a significant impact on the mechanical properties of concrete, but the replacement of ordinary fine aggregates with recycled fine aggregates had little effect on the overall performance. Lehner, P. and Horňáková, M. [ 10 ] examined the influence of fiber content and pre-compression stress on the chloride ion diffusion coefficient of recycled concrete structures.…”
Section: Introductionmentioning
confidence: 99%